2011
DOI: 10.1159/000332367
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Analysis of the Distribution of Endometriosis in Northwestern Italy

Abstract: Objective: The aim of this study is to estimate the incidence of endometriosis in a northwestern region of Italy. The potential sources of geographical variations in the incidence of endometriosis within the region are discussed. Methods: The patients selected were women between 18 and 45 years of age, born and residing in Piedmont who had undergone medical or surgical treatment for endometriosis between 2000 and 2005. The data were obtained from official hospital discharge records. Results: The number of wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
22
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 53 publications
5
22
2
Order By: Relevance
“…In addition, many women are asymptomatic and some lesions might heal spontaneously without a diagnosis having been previously made. [ 5 7 ]…”
Section: Introductionmentioning
confidence: 99%
“…In addition, many women are asymptomatic and some lesions might heal spontaneously without a diagnosis having been previously made. [ 5 7 ]…”
Section: Introductionmentioning
confidence: 99%
“…According to these controversies about risk factors associated with endometriosis and the effect of race and infertility in this regard, we planned this study to survey the relation between endometriosis and these suggested risk factors and establish a practical model in infertile Iranian women referred to Royan Institute and the infertility clinic of Arash Women's Hospital, two of the major referral centers of infertility in Tehran, Iran. As it was shown, the spatial incidence of endometriosis in some regions may be different due to environmental risk and presence of chemical pollutants [11]; therefore we selected studied women from these referral infertility centers in Tehran, the capital of Iran.…”
Section: Introductionmentioning
confidence: 99%
“…The main characteristics of the studies included in this review are shown in Table 1. The papers were published between 1989 and 2019 and originated from Norway [10], Denmark [11], the USA [12,16,19,20,25,26,33,35], Australia [13,14], Puerto Rico [15], Sweden [17], Japan [18], the UK [21,22], Israel [23], Germany [24], Iceland [27], Finland [28], Canada [29], Italy [30,32,34,36], and France [31]. The age of participating women varied in different studies from the minimal age of 10 years and older.…”
mentioning
confidence: 99%
“…The age of participating women varied in different studies from the minimal age of 10 years and older. The diagnosis of endometriosis was established mostly based on the diagnostic codes of International Classification of Diseases (ICD) [17,[20][21][22][23][24][25][26][27][28][29][30][31][32], self-reported data [10][11][12][13][14][15][16]18,19,35], and by surgery or image tests [33,36] or a combination of self-reported data and image tests [34].…”
mentioning
confidence: 99%